Pengaruh Suku Bunga dan Pembiayaan Bermasalah pada Bank Syariah - Aida, Farchati Umu; Yazid, Muhammad (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This journal discusses the influence of interest rates and problematic financing on the performance of Islamic banks in Indonesia. This research uses secondary data from Islamic bank financial reports. Sharia banking in Indonesia is one of the financial sectors that is increasingly developing. As a financial institution based on sharia principles. Islamic banks face risks that can affect their performance. The two main risks faced by Islamic banks are interest rate risk and financing problem risk. Interest rates have a significant influence on the profitability of Islamic banks. The increase in interest rates causes a decrease in the profitability of Islamic banks. Apart from that, problematic financing also has a negative impact on the performance of Islamic banks. The higher the level of problematic financing, the lower the profitability of Islamic banks. The implication of this research is that Islamic bank management needs to improve asset quality and strengthen risk management in order to reduce the negative impact of interest rate fluctuations and problematic financing on the performance of Islamic banks. Good risk management can help banks anticipate and manage the risks they face so that they can minimize their negative impact on bank performance. Apart from that, Islamic bank management also needs to diversify funding sources to reduce ethnic risk